A Note from the Field “Potlatch” Advancing a Health Survey: The Pen is Truly Mighty - J Johnson Ralph (Journal of Human Health Research, 2022)
Despite vast improvements in chemo-therapeutic interventions extensively extending the life span of patients with chronic and terminal diseases, there also is the unhappy extension of side- effects and adverse events. Thus, Health-Related Quality of Life (HR-QoL) becomes equally as important as length of life. Accurately, reliably, validly, and representatively measuring the on-going pulse beat of HR-QoL means ensuring optimal responses and response rates, which in turn means fostering and maximizing Survey Participants’ continued rapport, enlistment, engagement, and participation regarding HR-QoL research survey studies. This is generally true regarding all human subjects’ research. HR-QoL survey work at a nationally renowned Cancer Center recently identified an example of Potlatch or gift-giving (i.e., gifting), and its surrounding nuances, that were calculated and appear to evoke enhanced reciprocal engagement in a HR-QoL survey. This work involves continuous, iterative marketing study. The intent of this field note is to describe the methodological phenomenon that may have epistemological and theoretical relevance for ubiquitously advancing the interest of health survey research. Specifically, the contention will be that considered, and tactically deployed Potlatch can serve as a mechanism for facilitating and enhancing health survey research as well as enhancing stronger social engagement in research and treatment for patients undergoing medical care for long-term, chronic illness. First, it can rejuvenate and refocus Survey Participants’ involvement. Second, it can serve as an entrée and springboard to further forge a social connection in the interest of research. Lessons Learned and implications are reported.
Keywords: Gifts in Research